Gender preference on the quality of landscape aesthetic of urban agriculture - Diah Retno Dwi Hastuti; Rahim Darma; Darmawan Salman; Slamet Santosa; Triyatni Martosenjoyo; Novaty Eny Dungga (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
In addition to providing food benefits, urban agriculture also has aesthetic benefits. Therefore, a visual assessment of the urban agricultural landscape can be used to measure this aesthetic value. Gender preference is also carried out to see differences in visual assessment. This research was conducted in Makassar City using primary data with 129 respondents consisting of 53 people who had never been to Makassar and 76 people who had been/lived in Makassar. The aesthetic assessment of agricultural landscapes in Makassar City used the Scenic Beauty Estimation (SBE) method with a perceptual dimension. The results showed that the most beautiful urban agricultural landscapes had a high level of preference, namely in various plant gardens and verticultural hydroponic systems. Furthermore, the highest SBE score as a potential attraction was shown by male respondent who had never been to Makassar. Possible urban agricultural landscape resources should receive special attention by arranging them neatly and cleanly so that they have high artistic value to provide beauty and comfort for visitors.JEL Classification:  C00; O13; Q19